Diagnosis of Candidiasis and Hepatitis C virus in Thalasemia Patients - Qaid Mohammed Al-Kenani, Heyam; Abdul-Hussein Mejbel, Fatima (International Journal of Psychosocial Rehabilitation, 2020)
This research was performed with 96 male and female patients aged from one to fifty years, divided into 7 β-thalassemia patients with HCV infection and 89 β-thalassemia patients without HCV infection, who visited the Thalassemia Center at Al-Zahra Teaching Hospital in Al-Najaf, Iraq, for disease management, and 90 volunteer stable patients as a control group. Sample collection was conducted between April 2019 and the end of August 2019. This analysis tends to be 48 (48 percent) that offer Candida spp. a good outcome. Sabouraud dextrose agar (SDA) was cultivated from all the collected samples. The good finding cultivated on Chromagar that contained most of the isolates was also Candida albicans 43.75%, led by Candida parapsilosis 39.58%, Candida galabrata 10.41%, Candida tropicalis 2.08%, and 4.16% of unknown species. Some virulence factors in C. albicans, such as germ tubes and the formation of biofilm, were established in the present analysis. The findings showed that all C. albicans isolates were able to create germ tubes and develop biofilms. Conclusion: There is an association between HCV-thalassemia patients that showed a substantial difference at p = 0.05 between infected and non-infected classes. Once cultivated on chrom agar, the largest abundance of C. albicans than other animals.